A Frente Negra Pernambucana e sua proposta de educação para a população negra na ótica de um dos seus fundadores: José Vicente Rodrigues Lima - Década de 1930 - Silva, Fátima Aparecida (2008)
Research that analyses the Pernambucan Negro Movement in the 1930 decade, from a historic survey of the Pernambucan Negro Front, in the viewpoint of José Vicente Rodrigues Lima, one of its founders. In 1936, the Pernambucan Negro Front emerged in the capital city of Recife, and in 1937 it was transformed into the Afro-Brazilian Cultural Center, in action until today, now managed by Almerinda Rodrigues Lima, militant José Vicente Rodrigues Lima’s daughter. The main target of this thesis is to recover the social practices of the mentioned institution, which was organized in order to defend the Afro-descendants’ rights in the city of Recife in the 1930s. Therefore, by working out the individual memory of one of the Pernambucan Negro Front founders, this paper aims at doing a historical survey of this period’s anti-racist fight, with the purpose of understanding how members of such an organization regarded the negroes and the cultural output of African origin, as well as the political strategies then produced by its militants so that they could solve the social problems faced by the Negro population. Having in view the tight relations with the São Paulo (Paulista), Rio Grande do Sul (Gaúcha) and Pernambuco (Pernambucan) Negro Fronts, this research, on the one hand, eventually approaches a profitable exchange among their leaders, and on the other hand, tries to highlight the Pernambucan Negro Front idiosyncrasies, by developing reflections on the conditions of Negro communities in that time, whose members produced ways of reducing the racial inequalities by means of education and tense relations with the xangôs, a religion of African origin.